Analisis self-service station terhadap efektivitas aktivitas di restoran: Evaluasi ergonomi spasial di ruang publik - Andrianto Andrianto; Chris Chalik; Alvian Fajar Setiawan (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
Self-service programs in restaurants, such as the Budaya Beberes campaign, are initiatives designed to promote environmentally responsible behavior by encouraging active customer participation in cleaning food waste and managing leftovers independently. This concept not only contributes to environmental sustainability but also reflects a paradigm shift in modern restaurant service systems that emphasize efficiency, social responsibility, and user engagement. This study aims to evaluate the effectiveness and user comfort of self-service stations based on physical design elements that influence user experience and behavior. Employing a mixed methods approach with data triangulation, qualitative (behavioral observations and interviews) and quantitative (Likert-scale questionnaires analyzed via descriptive statistics), the research explores ergonomic issues in multifunctional furniture within public spaces. The findings indicate that non-strategic station placement, lack of clear visual signage, and overlapping spatial circulation reduce user comfort and potentially hinder customer participation in sustainability programs. The study highlights the importance of applying ergonomic design principles, clear spatial layouts, and informative visual guidance to create an effective, comfortable, and sustainable self-service experience within restaurant environments.